Nights of storytelling : a cultural history of Kanaky-New Caledonia - Ramsay, Raylene L. (University of Hawaiʻi Press, 2011)
Nights of Storytelling is the first book to present and contextualize the founding texts of New Caledonia, a country sui generis in the relatively little-known French Pacific. Extracts from literary, ethnographic, and historical works in English translation introduce the many voices of a diverse culture as it moves toward "independence" or the "common destiny" framed by the 1998 Noumea Agreements. These texts reflect the coexistence of two major cultures, Indigenous and European, shaped by the energies and shadows of empire and significantly influenced by one another. From the founding stories of Kanak oral tradition to the contradictory reports by Cook and d'Entrecasteaux, from the accounts of the French colony's difficult first destiny as a penal settlement to the construction of settler mythologies, the book investigates the nature of overlapping spaces created by cultural contact between Europe and the Pacific. The final section focuses on the literary effervescence of the contemporary period and its revisiting of colonial histories in the difficult movement toward a national identity. Historical romances describe the harshness of life for freed convicts, the impossibility of love between a liberated prisoner and a free settler. Sagas of late-nineteenth-century indentured laborers seeking a living on the nickel-rich main island speak similarly of physical struggle, sacrifice, and ultimately, of contribution to the country's development and the right to a place in the new land. Kanak texts disseminate that community's oral culture and largely silenced voice through the printed word. In a world still moving from colonial to postcolonial frames, the engagement of these works with vital contemporary questions of historical legacy, legitimacy, and cultural hybridity is intensely political. Aesthetics is a political ethics as the different communities of New Caledonia experiment with artistic and textual forms to write their distinctive place in the land. Nights of Storytelling is a collaborative work complemented by La nuit des contes, a subtitled DVD of images and text, which features key works read or spoken, generally in the original French. It provides visual and aural access for the book's Anglophone readers to the specific cultural, linguistic, and geographic contexts of these historical and literary works